Mild Hyperhomocystinemia In Children And Young Adults Were Placed On Dialysis: A Single Center Study - Naseri, Mitra; Mottaghi Moghadam Shahri, Hasan; Horri, Mohsen; Esmaeeli, Mohamad; Ghaneh Sherbaf, Fateme; Rasoli, Zahra; Salehi, Maryam; Salemian, Farzaneh; Jahanshahi, Shohre; Moeenolroayaa, Giti; et al. (Journal of Pediatric Nephrology, 2015)
Introduction: Hyperhomocysteinemia is common in end stage renal diseases. We aimed to determine the prevalence of hyperhomocysteinemia in dialysis cases and define independent risk factors of the development of hyperhomocysteinemia. Materials and Methods: The total plasma homocysteine values were measured in 46 dialysis patients including 20[43.4 %] girls and 26[56.6 %] boys aged 1.6-25 [19.9±6.5] years based on two different reference values for children [age dependent] and adults [cut off point of 15 µmol/L]. Results: Using the reference values for children, 26 cases [56.2 %] had hyperhomocysteinemia including 41.6% of CAPD and 2/3 of hemodialysis patients with no significant difference based on age, gender, duration and modality of dialysis, and dosage of folate supplement [p>0.05 for all]. Using a cut-off point of 15 µmol/L, hyperhomocysteinemia was reported in 30.4% of the patients including 11 hemodialysis and one CAPD [P=0.022], 10 out of 19 girls [52.6%%] and 4 out of 26 boys [15.4%] [p=0.063], but logistic regression analysis did not show any significant differences in the incidence rate of hyperhomocysteinemia according to the modality of dialysis and gender [P=0.998 and 0.137 respectively]. Conclusions: We found mild hyperhomocysteinemia as a common finding in dialysis patients; also, the prevalence of hyperhomocysteinemia was comparable in children and young adults. However, we noted that hemodialysis patients and females were more prone to more intense elevations of plasma homocysteine levels. We found that neither gender nor modality of dialysis played a role as risk factors for development of hyperhomocysteinemia in children and young adults. Keywords: Hyperhomocysteinemia; Child; Hemodialysis; Peritoneal dialysis; Adults.